Al-Asy'Ariyah (Sejarah Timbul, Abu Hasan al-Asy’ari dan Pokok-Pokok Ajarannya) - Beti Mulu (Al-'Adl, 2008)
In the history of Islamic thought development, it is generally known that there are two contradictory features of kalam's thought. The thought of the Mu'tazilite kalam has rational or logical thinking, whereas al-Ash'ariyyah has a traditional-style thought, kalam thought that does not give freedom of will and do to man, a small force for reason, the power of God's will that applies eternally -the absolute, and tied to the literal meaning in providing interpretation of the verses of the Qur'an. The thought of this kalam will give birth to traditional understandings of Islamic teachings and will foster sublime attitude fatalistic life in man. This understanding is found in the Ash'arite and Maturidiyyh Bukhara schools. Abu al-Hasan al-Ash'ari as the founder and founder of al-Ash'ari school, was originally a loyal follower of the Mutazilite doctrine, because of several things that contradicted his conscience, his thoughts and the social conditions of society (he felt the need to abandon that doctrine ) and even led to a new theology as a reaction against the teaching of the Mu'tazilites. In understanding the text, the Mu'tazilites used reason and then provided an interpretation of the text or the revelation according to reason. The Ash'ariah, on the contrary, first to the text of revelation and then bring the rational arguments to the text of the revelation. The Mu'tazilites used a lot of ta'wil or interpretation in understanding the texts of revelation, while the Ash'ariahs held much to the meaning of lafzi or texted from the text of revelation. In other words, the Mu'tazilites read the implicit in the text, the Ash'ariites read the explicit. At the end of the 3rd century, H appeared two prominent figures, Abu al-Hasan al-Ash'ari in Bashrah and Abu Mansur al-Maturidi in Samarkand. They were united in their denial of the Mu'tazilites. Ash'ariah is a Traditional theological school composed by Abu Hasan al-Ash'ari (935) in reaction to the Mu'tazila theology. In the classification of Islamic theology, Asy'ariah and Maturidiah are both called Sunnah Wal-Jamaah experts. Maturidiah flow is widely embraced by the Muslims who mazhab Hanafi Asy'ariah school is generally embraced by Muslims who mazhab Sunni